P220 IBIS-Q (IBd Identification of Spondyloarthrytis Questionnaire): a new tool to detect spondyloarthritis in inflammatory bowel diseases. (25th January 2019) - Variola, A; Di Ruscio, M; Geccherle, A; Pasetti, A; Cipriano, G; Zanolin, E; Marchetta, A; Tinazzi, I
Abstract: Background: Extraintestinal manifestations (EIM) are frequent in IBD and spondyloarthritis (SpA) are the commonest EIM (4%–23%). However, the reported delay to diagnosis ranges from 8 to 11 years. Early detection of SpA is clinically relevant to drive the therapeutic management. The aim of this study was to develop a questionnaire able to identify SpA in a cohort of IBD patients. Methods: During a preliminary meeting a group of experts in SpA-IBD (6 rheumatologists and 4 gastroenterologists) generated a list of 42 items able to cover all of possible manifestations of SpA, exploring spinal, articular and entheseal involvement. The questionnaire was tested on 20 patients with different levels of education with consequent elimination of 4 unclear items. Consecutive patients referring to our IBD Unit were enrolled from January to May 2018 without excluding patients affected by EIM. Patients affected by other rheumatic disease were excluded. The questionnaire was somministrated before the routine clinical assessment of the IBD Clinic. Rheumatologic assessment was performed in the same day by a rheumatologist blinded to the medical story and to the questionnaire results to (collect data about joint cunt of 66 SJ and 68 TJ, MASEI, LEI, presence of ASAS criteria for axial and pheripheral SpA, presence of diagnostic criteria for FM and NSLB pain mainly due to OA). If the patient presented a tender/swollen entheses an US examination completed the clinical examination. The patient completed BASDAI and BANSFI questionnaires in the same day. Factorial analysis to identify the main factors; ROC curves for sensibility/specificity; Youden index for cut-off were performed. Results: A final 38-items questionnaire was tested in 210 patients (excluding 17 patients for the presence of other rheumatic diseases and 12 for incomplete evaluation). The psychometric analysis of the questionnaire was done on data of 181 patients. Fifty-eight patients of the enrolled patients presented the ASAS criteria for the diagnosis of SpA (13 axial, 5 both axial and peripheral 40 peripheral). SpA prevalence in our cohort was 32% with 10 new cases detected by the questionnaire (5.5%: 7 peripheral and 3 axial). Psoriasis prevalence in our cohort of SpA: 36%. Through the psychometric and factorial analysis we selected 14-items to include in the final questionnaire (named IBIS-q) having a sensitivity 84.4% and specificity 80% to detect SpA (AUC 0.8803 with CI 95% 0.8305- 0.9301); we proposed as cut-off to identify SpA patients the presence of 4 positive questions of IBIS-q Conclusions: IBIS-q seems to be a useful and simple tool to use in our IBD clinic for the early referral of SpA, with a good statistical performance. Further studies are needed to validate this questionnaire.